Optimization of the ILCYM platform - Carhuapoma, Pablo; Gamarra, H.; Kreuze, Jan F. (2025)
This report documents the optimization of the ILCYM platform through the incorporation of the new “Complements” module, which reduces critical bottlenecks in data management, standardization, and preprocessing. The platform now integrates curated repositories of life tables, phenology, and climate data (FLT), improves reproducibility, and transforms complex outputs into actionable inputs for pest monitoring and management. With a roadmap that includes machine learning, integration with global databases, and visualization enhancements, the document aligns strongly with Resilient Agrifood Systems, Climate-smart Agriculture, and Regenerative Agriculture, solidifying ILCYM as a strategic CGIAR tool for plant health under climate change.